2021
DOI: 10.3389/fncel.2021.642211
|View full text |Cite
|
Sign up to set email alerts
|

Spike Generators and Cell Signaling in the Human Auditory Nerve: An Ultrastructural, Super-Resolution, and Gene Hybridization Study

Abstract: Background: The human auditory nerve contains 30,000 nerve fibers (NFs) that relay complex speech information to the brain with spectacular acuity. How speech is coded and influenced by various conditions is not known. It is also uncertain whether human nerve signaling involves exclusive proteins and gene manifestations compared with that of other species. Such information is difficult to determine due to the vulnerable, “esoteric,” and encapsulated human ear surrounded by the hardest bone in the body. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 140 publications
1
13
1
Order By: Relevance
“…5E). These findings contrast previous findings in mice, where Synj2 RNA was found to be expressed in the outer and [117] and is used here with permission. IHC = inner hair cell, OHCs = outer hair cells, Pv = Parvalbumin, cut.…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)contrasting
confidence: 94%
See 1 more Smart Citation
“…5E). These findings contrast previous findings in mice, where Synj2 RNA was found to be expressed in the outer and [117] and is used here with permission. IHC = inner hair cell, OHCs = outer hair cells, Pv = Parvalbumin, cut.…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)contrasting
confidence: 94%
“…The cells of Claudius were not labeled but are located above the cells of Boettcher. Image adapted with permission from Liu et al [117] the cochlea of the common marmoset, Callithrix jacchus [32]. We are also able to report EYA4 expression in the wall of the inner spiral sulcus.…”
Section: Eyes Absent Homolog 4 (Eya4)supporting
confidence: 52%
“…The technique that we used for sampling human tissue was previously described ( 18 ). Specimens were from patients suffering from life-threatening posterior cranial fossa meningioma compressing the brain stem ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that morphological and molecular divergences also exist among species ( Liu et al, 2009 ; Liu W. et al, 2021 ). Thus far, broad investigations of gene distribution and expression profiles in the human cochlea have not been presented.…”
Section: Introductionmentioning
confidence: 99%
“…NKA is a key ion transporter which maintains the EP and has been investigated in different species by several authors with somewhat different results ( Kuijpers and Bonting, 1969 ; Mees, 1983 ; Schulte and Adams, 1989 ; Ichimiya et al, 1994 ; Schulte and Steel, 1994 ; Keithley et al, 1995 ; Peters et al, 2001 ; Weber et al, 2001 ; McLean et al, 2009 ; Liu et al, 2019 ; Stephenson et al, 2021 ). Studies of NKA expression were performed previously in the human cochlea ( Weber et al, 2001 ; Liu et al, 2019 ; Liu W. et al, 2021 ; Stephenson et al, 2021 ). NKA is extensively expressed in human spiral ganglion somata, supporting its role in the relay and repolarization after spike activation ( Pivovarov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%